EFFECT OF ORGANIC CULTIVATION ON YIELD AND QUALITY OF LEMON BALM HERB (Melissa officinalis L.) - Katarzyna Seidler-Łożykowska; Romuald Mordalski; Wojciech Kucharski; Elżbieta Kędzia; Kamila Nowosad; Jan Bocianowski (Acta Scientiarum Polonorum: Hortorum Cultus, 2015)
The raw material of medicinal plants should fulfill the growing demands of herbal and cosmetic industries about its quality esp.: active substance content, sufficient yield, lack of pesticides and heavy metals residues and microbiologically clean. There-fore, more often organic origin of herbal raw material is welcome. The main aim of the experiment was evaluation and comparison the value of lemon balm herb from organic and conventional cultivation. In 2008–2010, in the field experiment, the yield and quality of lemon balm herb in organic cultivation were tested. The experiment was established in four different locations in Poland. The following features were evaluated: fresh and dried herb yields, seed yield, weight of 1000 seeds, essential oil content and its composition and microbiological contamination. Lemon balm herb yield from organic experiments was lower compared with the yield from conventional cultivation. The content of essential oil in both organic and conventional herbs were similar. The content of essential oil and its composition of lemon balm herb did not depend on localization. The content of two, main oil compounds: neral and geranial was higher in the conventional herbs. The satisfied yield of lemon balm seeds was obtained in organic experiments. The investigated lemon balm raw materials were below the level of standard contamination for raw materials treated with hot water (A) according to European Pharmacopoeia 7.0.